PENGARUH KOMPETENSI TERHADAP KINERJA PENYULUH PERTANIAN DI DINAS PERTANIAN PANGAN DAN PERIKANAN KABUPATEN TASIKMALAYA - Nuraeni, Dewi (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This research is based on the author's initial findings with a decrease in the yield of harvested rice, where production in Tasikmalaya Regency in 2020 was 780,350 tons, while in 2019 it reached 910,764 tons, meaning that there was a decrease in production of 14.32%. This is related to the competence of agricultural instructors that are still not optimal which results in less than optimal performance.This study aims to analyze the influence of competence on the performance of agricultural instructors at the Department of Agriculture, Food and Fisheries, Tasikmalaya Regency. This research is a survey research with a quantitative approach. The research instrument used by distributing questionnaires to 65 respondents, the results will be analyzed using simple linear regression analysis, this is because there is only one independent variable, namely the competence of agricultural instructors.The results of the study obtained data that competence affects the performance of agricultural instructors by 0,545 . This means that 54,5 % of agricultural instructor performance is influenced by competence and the remaining 45,5 % is influenced by other variables. The dimension of competence that has the greatest influence on the performance of agricultural extension workers is the attitude dimension.